Strategi Kepala Sekolah Dalam Membangun Karakter Cinta Tanah Air Siswa Melalui Program Budaya Nasionalis di SMKN 1 Ponorogo - Makrifatu Rodiana; Nur Rahmi Sonia (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
Principals have an important role in building students' patriotism through nationalist culture. In carrying out his role, the principal must also have strategies to achieve his program. This study aims to determine and explain 1) the form of the principal's strategy in building students' patriotism character through the nationalist culture program (2) the implementation of strategies in building students' patriotism character through the nationalist culture program 3) the implications of strategies in building students' patriotism character through the nationalist culture program. this research uses a qualitative approach with a case study type of research. Data collection techniques include interviews, observation and documentation. Data analysis techniques using Millies, Huberman and Saldana with data collection, data condensation, data presentation and conclusion drawing. The results of this study are 1) the principal's strategy in building the character of love for the country through the nationalist culture program, namely role modeling, habituation, stories, environmental reinforcement, rewards and punishments. (2) Implementation of strategies in building the character of love for the country through nationalist culture through subjects, self-development, and school culture. (3) The implications of the strategy in building the character of loving the country through the nationalist culture program can be seen from the output and outcome. Judging from the output, students make many achievements both academic and non-academic, students have good attitudes and characters that will be useful when they are in the world of work later. For the school, the result is that the school gets additional input. When viewed from the outcome, all residents of SMKN 1 Ponorogo have a sense of responsibility, have a sense of empathy, and have a high awareness to obey the rules and norms that exist in society.